ESTIMATION OF HERITABILITY OF FAMILIAL HYPERCHOLESTEROLEMIA AMONG 335 FAMILY MEMBERS OF FIVE HYPERCHOLESTEROLEMIC PROBANDS OF PAKISTANI POPULATION - Imtiaz, Fauzia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Familial hypercholesterolemia is an autosomal dominant disorder, caused by mutation in Low-density lipoprotein receptor (LDL-R) gene. Methods: Cross-sectional study conducted to recruit the population of Karachi-Pakistan, screened for familial hypercholesterolemia. A total of 1523 hypercholesterolemic individuals have taken part in the study, five were found to be familial hypercholesterolemia. Their lipids profile was estimated and a family pedigree was drawn. Results: Parentoffspring correlation, coefficient of linear regression, and heritability is calculated by using SPSS 12.0. A significant positive correlation of cholesterol was found among parents and their offspring (r=0.511, p=0.01, n=76). Coefficient of linear regression analysis also showed that parents-offspring relationship was highly significant at p<0.01 with b=0.438. Relationship between Father-Son, Father-Daughter, Mother-Son and Mother-Daughter were highly significant with b=0.794, 0.41, 0.766 and 0.56 respectively. Conclusion: The heritability among the parents and their offspring showed that genetic factors are major determinant of the familial resemblance in serum cholesterol among the Pakistani population living in the metropolitan area of Karachi. Keywords: Familial hypercholesterolemia, heritability, pedigree analysis